Prevalence of Domestic Violence among Pregnant Women in Gulmi District, Nepal - Marasini, Sabina; Sharma, Sudim; Maharjan, Manisha (One Health Journal of Nepal, 2022)
Introduction: Domestic violence (DV) is a substantial danger to pregnant women's physical and emotional health due to their heightened susceptibility during pregnancy, making it an important problem in public health campaigns. The main aim of this study was to identify the prevalence of domestic violence among pregnant women in Gulmi district. Methods: A descriptive cross-sectional study was conducted among 192 womens attending ANC visit in the district hospital of Gulmi District. A semi-structured questionnaire was used to obtain information related to socio-demographic characteristics and violence related characteristics. Data were entered and analyzed using SPSS version 20.0. Results were presented in frequency and percentage. Results: The prevalence of domestic violence was found to be 24.5%. Among the 47 cases of domestic violence, responses of emotional violence (21.9%) were highest followed by physical violence (18.2%) and sexual violence (10.9%). The majority of the perpetrators of violence were husbands (68.08%) followed by mothers-in-law (10.64%). Conclusions: The prevalence of domestic violence among the pregnant women in Gulmi district indicates an urgent need for specific protective measures, such as public awareness campaigns, social policy, and stronger legal reforms.